2020
DOI: 10.1038/s41598-020-78316-z
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: a necessary defense against extreme cadmium intoxication in a multigenerational 2D experiment

Abstract: Autophagy is a natural process that aims to eliminate malfunctioning cell parts, organelles or molecules under physiological conditions. It is also induced in response to infection, starvation or oxidative stress to provide energy in case of an energy deficit. The aim of this 2-dimensional study was to test if, and if so, how, this process depends on the concentration of cadmium in food (with Cd concentrations from 0 to 352 μg of Cd per g of food (dry weight)—D1 dimension) and the history of selection pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…Overall, autophagy's role in protecting from abiotic stressors such a desiccation, toxics, or direct oxidative damages in ectotherms has been highlighted numerous times (Moore et al, 2006, Bjedov et al, 2009Minois et al, 2012;Teets and Denlinger, 2013;Mizunoe et al, 2018;Zhang et al, 2019;Babczyńska et al, 2020, Valko et al, 2021. In the specific case of thermal stress, further correlations between autophagy genes upregulation and cold acclimation have been made (Gerken et al, 2015;Des Marteaux et al, 2017;Tachibana et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, autophagy's role in protecting from abiotic stressors such a desiccation, toxics, or direct oxidative damages in ectotherms has been highlighted numerous times (Moore et al, 2006, Bjedov et al, 2009Minois et al, 2012;Teets and Denlinger, 2013;Mizunoe et al, 2018;Zhang et al, 2019;Babczyńska et al, 2020, Valko et al, 2021. In the specific case of thermal stress, further correlations between autophagy genes upregulation and cold acclimation have been made (Gerken et al, 2015;Des Marteaux et al, 2017;Tachibana et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In response to stress, or exposure to rapamycin, inhibition of TOR has been linked to the upregulation of autophagy and downregulation of the synthesis of proteins that are not involved in the stress response, at the expense of cellular proliferation (Wullschleger et al, 2006). This contributes to the maintain of proteostasis, and autophagy has repeatedly been linked with enhanced tolerance to starvation, desiccation, heavy metals, toxic and oxidative damages in a variety of organisms, including insects (Moore et a., 2006;Bjedov et al, 2009, Minois et al, 2012Teets and Denlinger, 2013;Mizunoe et al, 2018;Zhang et al, 2019;Babczyńska et al, 2020, Valko et al, 2021. In the specific case of heat-stress, it has been demonstrated that activation of HSF-1 induces autophagy in multiple tissues in the ectothermic nematode Caenorhabditis elegans, which reduces protein denaturation and increases survival (Kumsta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy, a process of cellular self‐destruction in response to stress, starvation or infection, was usually related to apoptosis. But existing research only detected low intensity autophagy during multigenerational exposure (Babczynska et al, 2020; Dziewiecka et al, 2020), and the role of autophagy in multigenerational effects still need further study. In addition, due to the limitation in available evidence, it is largely unclear whether different pollutants including metals, organics, and particulate pollutants share the exact cellular mechanisms during controlling transgenerational toxicity.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…TOR inhibition can thus both directly mitigate the potential damages caused by abiotic stress through autophagy induction, while also improving cellular metabolic robustness and survival by maximizing ATP and metabolite availability at the expense of cellular proliferation and organismal growth [38,43]. Accordingly, increased survival upon exposure to various stressors such as starvation, desiccation, toxins, oxidative damage, and cold exposure has been correlated with modulation of autophagy in ectotherms [21,22,41,[44][45][46][47][48][49][50][51][52][53]. In the specific case of heat-stress, it has been demonstrated that activation of the transcription factor HSF-1, which controls the cellular heat-shock response and transcription of heat-inducible Hsps, also induces autophagy in multiple tissues in Caenorhabditis elegans [13].…”
Section: Introductionmentioning
confidence: 99%